Ismuba Curriculum: the Effort to Prevent Intolerance within Muhammadiyah High School Students - Betty Mauli Rosa Bustam; Rika Astari; Aris Widada (UIN Sunan Ampel Surabaya, 2021)
ISMUBA is an acronym of al-Islam, Muhammadiyan, and Arabic teaching, is a combination of compulsory subjects that are the peculiarities and advantages of Muhammadiyah schools-madrasahs compared to other schools-madrasahs. The ISMUBA curriculum follows the level of education from elementary to high school. Related to the rise of social phenomena that linked to deviations in the application of Islamic religious teachings in Indonesian society, one of which became a polemic, namely intolerance, the existence of ISMUBA became significant to review. This is because Muhammadiyah has more than a thousand high school-level schools-madrasah spread throughout Indonesia, so it is worth exploring how the ISMBA curriculum affects learning about tolerance for adolescents. The research method used in this research is a qualitative method with a literature review approach. Literature review in this study using integrative reviews Baumeister & Leary. The results of this study show that the ISMUBA curriculum has contained material related to tolerance and invitations to appreciate the differences that Allah Swt. has created, but the arguments that support this issue still need to be added. For example, the main proposition used in the learning of tolerance, refers to verses 10 and 12 of Surat al-Hujurat, but does not include verse 11. This makes the explanation of the aspects that students should avoid in order to be tolerant less comprehensive.